Somatostatin-SSTR3-GSK3 modulates human T-cell responses by inhibiting OXPHOS - Zhang, Bo; Feng, Huiru; Lin, Hui; Li, Rui (Frontiers in Immunology, 2024)
Introduction Somatostatin (SST) is a peptide hormone primarily synthesized in the digestive and nervous systems. While its impact on the endocrine system is well-established, accumulating evidence suggests a crucial role for SST and its analogues in modulating immune responses. Despite this, the precise mechanism through which SST regulates T cells has remained largely unknown. Methods To elucidate the impact of SST on human T cells, we conducted a series of experiments involving cell culture assays, molecular analyses, and metabolic profiling. Human T cells were treated with SST, and various parameters including proliferation, cytokine production, and metabolic activities were assessed. Additionally, we employed pharmacological inhibitors and genetic manipulations to dissect the signaling pathways mediating SST's effects on T cells. Results We showed that SST diminishes T-cell proliferation by influencing IL-2 production and T-cell mitochondrial respiration, while having no discernible impact on TCR-induced glycolysis. Our findings also identified that the regulatory influence of SST on T-cell responses and metabolism is contingent on its receptor, SSTR3. Moreover, we demonstrated that SST governs T-cell responses and metabolism by acting through the T-cell metabolic checkpoint GSK3. Discussion Our study provides novel insights into the immunoregulatory function of SST in human T cells, highlighting the complex interplay between hormonal signaling and immune regulation. Understanding the molecular mechanisms underlying SST's effects on T cells may offer therapeutic opportunities for manipulating immune responses in various pathological conditions.